2020
DOI: 10.1002/brb3.1889
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in default mode network correlates with severity of hypoxemia in obstructive sleep apnea

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…A task-state MRI study demonstrated that the DMN pattern observed in OSA patients showed more deactivated areas and reduced brain activation than that observed in HC (Ayalon et al, 2009;Prilipko et al, 2011). Another study showed that impaired cognitive function and attention in patients with OSA was associated with DMN dysfunction, and it is believed that the main factor is hypoxemia (Chang et al, 2020a). Moreover, DMN impairment has been shown to be an important factor (Cheng et al, 2020;Wang et al, 2020;Qin et al, 2021) and plays a pivotal role in cognitive function (Smallwood et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A task-state MRI study demonstrated that the DMN pattern observed in OSA patients showed more deactivated areas and reduced brain activation than that observed in HC (Ayalon et al, 2009;Prilipko et al, 2011). Another study showed that impaired cognitive function and attention in patients with OSA was associated with DMN dysfunction, and it is believed that the main factor is hypoxemia (Chang et al, 2020a). Moreover, DMN impairment has been shown to be an important factor (Cheng et al, 2020;Wang et al, 2020;Qin et al, 2021) and plays a pivotal role in cognitive function (Smallwood et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In OSA patients, reduced FC in the pre-DMN and compensatory higher FC in the post-DMN have been reported [51]. A previous study has found that OSA patients exhibit abnormalities in FC between several DMN subregions and abnormalities in spontaneous activity and that these FC changes are related to the severity of OSA and degree of hypoxia [70][71][72][73]. A longitudinal study found that CPAP could effectively improve cerebral function by increasing DMN connectivity [74].…”
Section: Discussionmentioning
confidence: 99%
“…et al 10.3389/fnagi.2022.1022628 Frontiers in Aging Neuroscience 06 frontiersin.org is a group of brain regions, including the anterior and medial frontal cortex, bilateral temporal lobes, precuneus, and lateral parietal cortex, that are associated with social behavior, emotional control, memory, learning, and task execution (Raichle, 2015). Ya-ting Chang et al showed that reduced functional connectivity in the DMN was associated with nocturnal hypoxemia rather than sleep rhythms (Chang et al, 2020). Our previous studies have shown that decreased FC between the DMN and the central executive network and decreased functional connectivity between brain networks are associated with delayed memory (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%